2002
DOI: 10.1515/znc-2002-7-831
|View full text |Cite
|
Sign up to set email alerts
|

Further Halotyrosine Derivatives from the Marine Sponge Suberea aff. praetensa

Abstract: Reexamination of the marine sponge Suberea aff. praetensa, (Row) from the Gulf of Thailand furnished in addition to bromotyrosine derivatives found previously 5-bromo-and 5-chlorocavernicolin, cavernicolins 1 and 2, two other brominated tyrosine metabolites, a known bisoxazolidone and a new unusual rearranged tyrosine metabolite subereatensin. Several of the metabolites exhibited significant inhibitory effects against five human cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 1 publication
(4 reference statements)
0
23
0
Order By: Relevance
“…Prepsammaplin A (155) and psammaplins B (156), C (157), and D (158) were isolated from the marine sponge Psammaplysilla purpurea by Jimenez and Crews (110). The isolation of prepsammaplin A (155), a cysteine dimer, indicated that cysteine might be the precursor of the central part of psammaplin A. Interestingly, the R functional groups of psammaplin B (156) and C (157) are unique and do not appear to have counterparts among any known marine sponge amino acid derivatives (110).…”
Section: Oxime-histamines-ianthellinmentioning
confidence: 99%
See 2 more Smart Citations
“…Prepsammaplin A (155) and psammaplins B (156), C (157), and D (158) were isolated from the marine sponge Psammaplysilla purpurea by Jimenez and Crews (110). The isolation of prepsammaplin A (155), a cysteine dimer, indicated that cysteine might be the precursor of the central part of psammaplin A. Interestingly, the R functional groups of psammaplin B (156) and C (157) are unique and do not appear to have counterparts among any known marine sponge amino acid derivatives (110).…”
Section: Oxime-histamines-ianthellinmentioning
confidence: 99%
“…Crews et al proposed a biogenetic pathway, based on the isolation of prep-sammaplin A (155), to rationalize the formation of psammaplin A (152) and other bromotyrosine derivatives isolated from Pseudoceratina purea by his group (110,112). A straightforward dimerization of a rearranged cysteine (Cys′=HS-CH 2 -CH 2 -NHCOOMe) could generate prepsammaplin A (155).…”
Section: Biosynthesis Of Psammaplin Type Of Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…And we expanded this assay for several other similar studies for tyrosine modifications. Because tyrosines that are post-translationally modified by nitrating oxidants, brominating oxidants, and chloramination oxidants produced from macrophages, neutrophils or eosinophils to form nitrotyrosine, bromotyrosine and chlorotyrosine respectively, have relevance to breast cancers (17)(18)(19)(20)(21)(22)(23). For example, hypochlorous acid/hypochlorite adducts have been reported for breast cancer (24)(25)(26)(27).…”
Section: Body Develop and Validate Ptm-elisa Microarraymentioning
confidence: 99%
“…praetensa). 9 While 3-bromoverongiaquinol (1) displayed bactericidal properties against Streptococcus faecalis and Bacillus subtilis, 7 5-monobromocavernicolin (2) represents the first example of a marine natural product isolated in almost racemic form (6% ee) which was shown to inhibit the growth of Sarcina lutea, Bacillus subtilis, Alcaligenes faecalis and Proteus vulgaris. 8 Racemic 3-bromoverongiaquinol (1) has been previously prepared twice via anodic oxidation, albeit in very low yields (2.5 and 6.3% yield), 7,10 and the relative configuration of 5-monobromocavernicolin (2) was proposed based solely on spectroscopic and mass spectrometry data as no total synthesis has been reported so far.…”
Section: Introductionmentioning
confidence: 99%